Hubungan Pengetahuan dan Karakteristik Wanita Usia Subur (WUS) Terhadap Perilaku Deteksi Dini Kanker Serviks - Fithriyah Mutammimah; Nunung Nurjanah; Nisa Rizki Nurfita (Jurnal Rumpun Ilmu Kesehatan, 2023)
Cervical cancer is the second largest cancer in women with an estimated 445,000 new cases (84% of new cases in the world) and causes 87% of deaths in women in developing countries. This is due to the behavior of women who do not routinely detect cervical cancer, one of which is the IVA method. The coverage of IVA examinations in West Java province until 2016 was 205,421 people (3%). In Cirebon Regency from 2015-2016, 289 people were recorded who had been examined for early detection of cervical cancer, which means that the coverage of early detection examinations in Cirebon district was still below 1%. This research is a type of analytic observational research. The design used is cross sectional. The sample of this research is 40 respondents. The research instrument used was a questionnaire. The results showed that there was a significant relationship between the level of knowledge, attitudes, age characteristics and employment status with early detection of cervical cancer. There is no significant relationship between education and parity with early detection of cervical cancer. The conclusion from this study is that there is a significant relationship between the level of knowledge and characteristics of WUS with early detection behavior. It is hoped that midwives can carry out health promotion efforts to increase knowledge so that women of childbearing age carry out early detection of cervical cancer to prevent cervical cancer.